Generic versus small-sided game training in soccer - Hill-Haas, S. V.; Coutts, A. J.; Rowsell, G. J.; Dawson, B. T. (International Journal of Sports Medicine, 2009)
The aim of this study was to compare 7 weeks of soccer-specific small-sided game (SSG) and mixed generic fitness training, on selected physiological, perceptual and performance variables. Twenty-five elite youth players were randomly allocated to either a SSG (coach selected) or generic training group (GTG), in a randomised, parallel matched-group design. In addition to normal training, each group completed two fitness training sessions per week of equal duration. Players completed a V?O2 max treadmill test, Multistage Fitness Test (MSFT), Yo-Yo Intermittent Recovery Test Level 1 (YYIRTL1), 12×20 m test of repeated-sprint ability (RSA) and 20-m sprint test pre and post training. Training heart rate, perceived training intensity and perceptual fatigue measures were recorded throughout the training period. There were no differences in training heart rate or perceptual well-being measures. However, the GTG did perceive their training to be more intense than SSG. There were no changes in either group for V?O2 max, MSFT, RSA or sprint performance. However, there were improvements in YYIRTL1 performance for both groups over time, but not between groups. The results show that both types of training are equally effective at improving pre-season YYIRTL1 performance, despite GTG being perceived to be more intense.